2013
DOI: 10.1016/j.jep.2013.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of Total Saikosaponins of Bupleurum yinchowense on corticosterone-induced apoptosis in PC12 cells

Abstract: The result depicted that antidepressant-like effect of TSS in vivo may be associated with the cytoprotection of neuron, and the neuroprotective mechanisms were correlated with inhibiting the ER stress and the mitochondrial apoptotic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 34 publications
4
31
0
Order By: Relevance
“…4 and 5). These results are in agreement with previous findings that mostly focused on Ca 2+ and mitochondrial function [25,29,35,36]. Perhaps the most significant finding in the present study was that both an increase in cytosolic Ca 2+ concentration and disruption of mitochondrial function following exposure to CORT were blocked by subsequent CSA treatment, suggesting that CSA may exert a neuroprotective effect through the blockade of [Ca 2+ ] i overload and mitochondrial dysfunction (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4 and 5). These results are in agreement with previous findings that mostly focused on Ca 2+ and mitochondrial function [25,29,35,36]. Perhaps the most significant finding in the present study was that both an increase in cytosolic Ca 2+ concentration and disruption of mitochondrial function following exposure to CORT were blocked by subsequent CSA treatment, suggesting that CSA may exert a neuroprotective effect through the blockade of [Ca 2+ ] i overload and mitochondrial dysfunction (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, it has been reported that CORT induces apoptosis in cultured hippocampal neurons through the blockade of p38 MAPK activation and the induction of mitochondrial dysfunction, including increasing ∆Ψm and inhibiting caspase-3 activation [28]. Furthermore, CORT was shown to be involved in the fragmentation of DNA, the induction of Bax/Bcl-2, Ca 2+ deregulation, the abnormal opening of mPTPs and the disruption of ∆Ψm in PC12 cells [29]. Here, we describe a protective effect by which naturally occurring CSA ameliorates CORT-induced neurotoxicity in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed that GRP78 expression increased at both the mRNA and protein levels in the group that only received irradiation. While the combination of low-dose GEN treatment with irradiation inhibited GRP78 over-expression, it appears that GEN may exert its radioprotective activity through the alleviation of the ER stress response via GRP78 down-regulation [38].…”
Section: Discussionmentioning
confidence: 97%
“…14 In recent years, Radix Bupleuri and saikosaponins have been demonstrated to possess antidepressant effects in in vivo and in vitro experiments. [15][16][17][18] A study published in Neuroscience Letters in 2017 demonstrates that administration of saikosaponin A for 4 weeks could produce the antidepressant-like effects in perimenopausal rats, and the potential mechanism may be the restoration of neuroendocrine, neuroinflammation and neurotrophic systems in the hippocampus during perimenopausal. 19 These results indicate that there is a strong correlation between SA and depression, but the exact therapeutic mechanisms of SA on depression need to be further explored.…”
Section: Introductionmentioning
confidence: 99%